The DHA supplementation during pregnancy: benefits and risks - review - Justyna Dutkiewicz; Wiktoria Mączyńska; Michał Wijata; Anna Maria Wijata; Zuzanna Adriana Przybyłek-Stępień; Ryszard Bartosiński; Jan Szustak; Maria Kąpa; Bartosz Szepietowski; Jakub Marek Kaźmierczak; Ewelina Rycerz; Piotr Pasek (Journal of Education, Health and Sport, 2025)
Pregnancy is a special period in a woman's life that requires special attention. For the proper development of the foetus and the maintenance of the mother's health, a balanced diet and appropriate supplementation are extremely important. One of the key nutrients is docosahexaenoic acid (DHA), which belongs to the group of polyunsaturated omega-3 fatty acids. The present paper reviews the literature on the biological significance of DHA during pregnancy, as well as the sources of this nutrient and its requirement. The benefits of taking DHA are also presented. The potential risks and limitations of DHA supplementation are discussed, including the risks of contaminants present in fish products. International recommendations and future research directions are also presented, highlighting the need for further analysis of the impact of DHA on the long-term health of both mother and child.